(untitled) (Bioagro, 2022)
Environmental conditions during the growth of Vicia faba plants and post-harvest processing methods influence its contents of secondary metabolites. In this study, total phenolic compounds (TP) and total flavonoids (TF) were quantified in broad bean plants at 10, 15 and 20 days after emergence (DAE), in floral buds and open flowers developed in the field or in a greenhouse with soil (GH-S) or tezontle (GH-T) as substrate. The effects of post-harvest processing, namely oven-drying and freeze-drying, were also evaluated. The analysis of variance showed, in all growth conditions, that the content of TP and TF varied significantly (P≤0.05 or P≤0.01) according to the age of the plant or the flowering stage, the processing methods and the interaction between those factors. Field-grown plants at 10, 15 and 20 DAE exhibited a higher mean value of TP (113.55 mg·g·-1 of gallic acid equivalent) and TF (126.60 mg·g·-1 of quercetin equivalent) with oven-dried samples, compared with those plants harvested in GH-S and GH-T conditions. Drying in the oven was most efficient in conserving phenolic compounds in field plants while freeze-drying preserved the levels of metabolites in greenhouse plants more effectively. In order to obtain the maximum content of phenolic compounds in minimal time, it is suggested to grow broad beans in the field, harvest plants at 10 DAE, and process them by oven-drying.